2010
DOI: 10.1515/hf.2010.027
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of syringyl quinone methide intermediates in dehydrogenative polymerization. Part 2: pH effect in horseradish peroxidase-catalyzed polymerization of sinapyl alcohol

Abstract: The solvent pH effect in the horseradish peroxidase (HRP)-catalyzed polymerization of sinapyl alcohol (S-alc) and analogously, sinapyl alcohol g-O-glucoside (isosyringin, iso-S) was investigated particularly focusing on the behavior of syringyl-type quinone methide intermediates (S-type QMs) under acidic conditions. At first, the HRP-catalyzed polymerization of iso-S at pH 6.5-2.5, which produces watersoluble dehydrogenation polymer (DHP) intermediates in a homogeneous phase, was monitored by UV spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…It is reported that in the quinone methide reactions with vanillyl alcohol in aqueous solution, only the addition of water was observed at low pH, and the phenol addition was prominent under neutral conditions . A similar pH effect has been reported for the dehydrogenative polymerization of SA using HRP . These results suggest that in the biosynthesis of lignin, the type of laccase does not significantly affect the structure of lignin.…”
Section: Results and Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It is reported that in the quinone methide reactions with vanillyl alcohol in aqueous solution, only the addition of water was observed at low pH, and the phenol addition was prominent under neutral conditions . A similar pH effect has been reported for the dehydrogenative polymerization of SA using HRP . These results suggest that in the biosynthesis of lignin, the type of laccase does not significantly affect the structure of lignin.…”
Section: Results and Discussionsupporting
confidence: 75%
“… 27 A similar pH effect has been reported for the dehydrogenative polymerization of SA using HRP. 28 These results suggest that in the biosynthesis of lignin, the type of laccase does not significantly affect the structure of lignin. It is likely that the surrounding environment during lignin biosynthesis, such as pH, has a greater influence on the structure of lignin.…”
Section: Results and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Therefore in the present study, we examined the copolymerization of EGCG and CA into dehydrogenation polymers (synthetic lignins, DHPs), utilizing an in vitro horseradish peroxidase (HRP)-catalyzed polymerization system that models lignin polymerization in vivo [ 35 - 38 ]. Two-dimensional nuclear magnetic resonance (NMR) experiments with the DHPs revealed one major cross-coupling mode between CA and both epigallocatechin and gallate moieties of EGCG.…”
Section: Introductionmentioning
confidence: 99%